2018
DOI: 10.1016/j.clon.2018.02.067
|View full text |Cite
|
Sign up to set email alerts
|

Stomach Dose–Volume Predicts Acute Gastrointestinal Toxicity in Chemoradiotherapy for Locally Advanced Pancreatic Cancer

Abstract: In chemoradiotherapy for LAPC the volume of stomach irradiated to a moderately high dose (35-45 Gy) predicts the incidence and severity of acute toxicity. Other predictive factors can include age, sex, recent weight loss and concomitant chemotherapy agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…More quantitative information was reported in the contexts of conventionally fractionated radiotherapy (i.e., 1.8-2.0 Gy/fr) and SBRT (delivered in 1-5 fractions). Concerning conventional fractionation, most studies were consistent in suggesting a prevalent dose effect when considering moderate/ severe duodenal and gastric toxicities, with the risk rapidly increasing for prescribed doses above 55-60 Gy and fractions of duodenum/stomach receiving more than 35-55 Gy above few %/few to tens of cubic centimeters (28,(36)(37)(38)(39)(40): similar findings were suggested for mild hypofractionation (2.15-2.25 Gy/fr) in a cohort of 105 patients treated with intensity-modulated radiotherapy (IMRT) for esophageal cancer at 60.2 Gy (29). Regarding SBRT, safe constraints for stomach and duodenum were suggested for one/three/five fractions, with quite consistent recent updates based on patient data, mostly for the duodenum with the 5-fraction scheme, as reviewed by Cattaneo and Marrazzo (36).…”
Section: Discussionmentioning
confidence: 88%
“…More quantitative information was reported in the contexts of conventionally fractionated radiotherapy (i.e., 1.8-2.0 Gy/fr) and SBRT (delivered in 1-5 fractions). Concerning conventional fractionation, most studies were consistent in suggesting a prevalent dose effect when considering moderate/ severe duodenal and gastric toxicities, with the risk rapidly increasing for prescribed doses above 55-60 Gy and fractions of duodenum/stomach receiving more than 35-55 Gy above few %/few to tens of cubic centimeters (28,(36)(37)(38)(39)(40): similar findings were suggested for mild hypofractionation (2.15-2.25 Gy/fr) in a cohort of 105 patients treated with intensity-modulated radiotherapy (IMRT) for esophageal cancer at 60.2 Gy (29). Regarding SBRT, safe constraints for stomach and duodenum were suggested for one/three/five fractions, with quite consistent recent updates based on patient data, mostly for the duodenum with the 5-fraction scheme, as reviewed by Cattaneo and Marrazzo (36).…”
Section: Discussionmentioning
confidence: 88%
“…On the other hand, Holyoake et al. reported that the volume of the ST that was irradiated with a moderately high dose (35–45 Gy) was a predictive factor of acute GI toxicity [ 27 ]. ST V40 and ST V30 were also identified as predictive factors in the present study, and a moderate dose to the ST was also shown to be a predictive factor of acute GI toxicities in a study on hypofractionation RT for pancreatic cancer [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A generalized equivalent uniform dose (gEUD) of 46 Gy is associated with a 20% bleeding risk in patients without cirrhosis, while a gEUD of only 18 Gy is associated with a 20% bleeding risk in patients with cirrhosis [11]. Other than cirrhosis, old age, concurrent chemotherapy, and Helicobacter pylori -induced gastritis were reported as risk factors that can lower the threshold dose of the stomach [15]. In the present study, age was the only significant risk factor for hemorrhagic gastric disease.…”
Section: Discussionmentioning
confidence: 99%